2012
DOI: 10.5144/0256-4947.2012.30.5.1342
|View full text |Cite
|
Sign up to set email alerts
|

Granular cell ameloblastoma showing desmoplasia

Abstract: Our case of ameloblastoma had a surprisingly long 25 year history, with abnormally large dimensions, a multilocular diffuse-mixed radiographic picture, and was histopathologically diagnosed as granular cell ameloblastoma with desmoplasia. To the best of our knowledge, this is the first ameloblastoma ever reported, that has shown combined features of granular cells, desmoplasia, ameloblastic follicles, plexiform, and acanthomatous patterns. The nature of granular cells in this type of tumor and the significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The granular cells are a transitional or matured phase in the life cycle of ameloblastomas, starting with normal stellate reticulum-like cells, leading to a production of granules and finally resulting in degeneration and the formation of cystic areas, differing from the aggressive tumor nature reported previously 44. However, the granular cell type is rare and accounts for only 4% of ameloblastomas 45…”
Section: Ameloblastomamentioning
confidence: 98%
“…The granular cells are a transitional or matured phase in the life cycle of ameloblastomas, starting with normal stellate reticulum-like cells, leading to a production of granules and finally resulting in degeneration and the formation of cystic areas, differing from the aggressive tumor nature reported previously 44. However, the granular cell type is rare and accounts for only 4% of ameloblastomas 45…”
Section: Ameloblastomamentioning
confidence: 98%
“…Granular cell ameloblastoma accounts for approximately 3.5%-5% of all ameloblastoma. [11][12][13] Hartman reported that the average age of the patients at the first visit was 40.7 years and that there was no difference between genders in his 20 cases. 11 The WHO classification of odontogenic tumors mentions that granular ameloblastomas are characterized by granular cells located within the center of the follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Granular cell ameloblastoma accounts for approximately 3.5%–5% of all ameloblastoma . Hartman reported that the average age of the patients at the first visit was 40.7 years and that there was no difference between genders in his 20 cases .…”
Section: Discussionmentioning
confidence: 99%
“…The Granular cell ameloblastoma (G.C.A) once considered as the most aggressive variant of ameloblastoma but according to the recent studies it is believed that the earlier belief was a myth. 14 Numerous theories have been proposed on the origin and nature of these granular cells in ameloblastomas. The granular cells are epithelial in origin and several ultrastructural studies describe them as lysosome.…”
Section: Discussionmentioning
confidence: 99%